The Prevalence of Echocardiographic Accretions on the Leads of Patients with Permanent Pacemakers - Dundar, Cihan; Tigen, Kursat; Tanalp, Cevat; Izgi, Akin; Karaahmet, Tansu; Cevik, Cihan; Erkol, Ayhan; Oduncu, Vecih; Kirma, Cevat (Journal of the American Society of Echocardiography, 2011)
The aim of this study was to investigate the prevalence and clinical significance of echocardiographic “accretions” on intracardiac leads in patients with permanent pacemakers. Two hundred eleven patients with permanent cardiac pacemakers implanted between 1988 and 2005 were called by telephone to participate in this study. The cohort was identified retrospectively and followed prospectively after recruitment. Seventy-five patients who agreed to participate in the study were examined by using transthoracic and transesophageal echocardiography for the detection of pacemaker lead accretions. Blood samples were also obtained for aerobic and anaerobic cultures, high-sensitivity C-reactive protein, erythrocyte sedimentation rate, and complete blood count. The medical records of the patients were analyzed carefully, and patients were called by telephone to investigate mortality and clinical events after 5 years of follow-up. The initial study group included 28 women and 47 men (mean age, 60 ± 15 years). At least one echocardiographic accretion on the pacemaker leads was identified in 16 subjects (21%) by transthoracic echocardiography and in 21 subjects (28%) by transesophageal echocardiography. All accretions were in the right atrial portion of the leads, whereas the ventricular segments of the leads were free of accretions. Patients with pacemaker lead accretions were significantly younger than those without accretions ( P = .03). At 5-year follow-up, information could be obtained from 60 of the 75 patients. Among these 60 patients, 28 (46%) had died. There was no difference in mortality between patients who did and did not have lead accretions ( P = .96). Patients who died during follow-up were older ( P < .001), had shorter time intervals from pacemaker implantation to study enrollment ( P = .002), had increased left atrial ( P = .007) and right atrial ( P = .04) sizes, and had higher pulmonary artery systolic pressures ( P = .012) than those who were alive at 5 years. Logistic regression analysis revealed that age and pulmonary artery systolic pressure were independent predictors of mortality. Accretions on permanent pacemaker leads can be detected by both transthoracic and transesophageal echocardiography. Follow-up data did not demonstrate any effect of these accretions on 5-year survival.